Muscle damage in resistance training - Is muscle damage necessary for strength gain and muscle hypertrophy?- - Nosaka, K.; Lavender, A.; Newton, M.; Sacco, P. (International Journal of Sport & Health Science, 2003)
The objectives of this review are to delineate muscle damage induced in resistance training, discuss how muscle damage is associated with increases in strength and/or muscle crosssectional area, and clarify whether "pain " is necessary for " gain " in muscle function and muscle volume in resistance training. Resistance training induces muscle damage, especially in the initial phase of training when unaccustomed eccentric actions are performed. Muscle damage is best indicated by loss of muscle strength and range of motion, and delayed onset muscle soreness does not necessarily reflect the magnitude of muscle damage. Resistance training employing eccentric biased exercises has potential for increasing not only eccentric strength but also isometric strength, and seems to be superior to exercise based solely on concentric actions. Since muscle damage and soreness are induced to a greater extent in eccentric muscle actions than with isometric or concentric actions, it is believed that muscle damage is necessary for size and strength gain. However, it appears that muscles become less susceptible to muscle damage as training progresses. We concluded that muscle damage and/or muscle soreness are not necessarily indispensable for exercise-induced muscle adaptation.